Interaction of forming temperature and grain size effect in micro/meso-scale plastic deformation of nickel-base superalloy. (15th March 2016) - Zhao, R.; Han, J.Q.; Liu, B.B.; Wan, M.
Abstract: In high temperature meso/micro plastic forming process, material yield and deformation are quite different from those at atmospheric temperature. The flow stress decreases quite obviously by the raise of forming temperature and is also modified by the change of inner grain numbers. Moreover, the traditional micro-forming theory is often crippled or rendered totally inefficient under thermal condition due to the interacted effects. To explore the coupled effect of grain size and deformation temperature on thermally-aided meso/micro-scale plastic deformation, uniaxial tensile tests of Inconel 718 sheets with different inner grain sizes are performed at diverse temperatures. The experimental results reveal that both yield stress and flow stress decrease with the increasing particle size and temperature. A strong grain size effect emerges at atmospheric temperature, while decays with the increase of deformation temperature. In addition, an exponential relationship between intercept stress and deformation temperature is established at specific strain level, while the slope decreases with the increasing temperature as well as the deformation strain level, which could be interpreted by the dislocation theory and the grain boundary strengthening effect. Furthermore, a modified Zerilli–Armstrong model is proposed to describe the flow stress considering the deformation temperature and grain size simultaneously. The research thus provides an in-depth understanding of the interactive effect of deformation temperature and material microstructure in meso/micro-scale plastic deformation. Graphical abstract: Highlights: Hall–Petch format curves at diverse temperatures are fitted and compared. The variation of intercept stress and slope in HP equation is sufficiently analyzed. An exponential relation is found in intercept stress with temperature at specific strain levels. The slope k decreases with the temperature as well as the deformation degree. A modified Zerilli-Armstrong model is proposed describing the coupled effect.